1967
DOI: 10.1128/jb.93.5.1499-1508.1967
|View full text |Cite
|
Sign up to set email alerts
|

Oligopeptide Uptake by Bacteroides ruminicola

Abstract: Bacteroides ruminicola did not take up 14C from exogenous "C-labeled L-proline or 14C-labeled L-glutamic acid and took up very little 14C from exogenous 4C-labeled L-valine. Growing cultures of B. ruminicola rapidly took up 14C from "4C-prolinelabeled peptides of molecular weights up to 2,000 and incorporated it into trichloroacetic acid-insoluble cell material. Uptake and incorporation did not occur at 0 C and were reduced or eliminated in glucose-starved cells, depending upon the length of time the cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…The ability of microorganisms to assimilate peptides instead of free amino acids is energetically advantageous, and would be physiologically important in an energy de¢cient environment such as the large intestine. Peptide stimulation of growth has been observed in Prevotella ruminicola [9], but is not only con¢ned to single isolates, since mixed cultures of rumen microorganisms have been shown to utilise N from ammonia or peptides, but not from amino acids [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of microorganisms to assimilate peptides instead of free amino acids is energetically advantageous, and would be physiologically important in an energy de¢cient environment such as the large intestine. Peptide stimulation of growth has been observed in Prevotella ruminicola [9], but is not only con¢ned to single isolates, since mixed cultures of rumen microorganisms have been shown to utilise N from ammonia or peptides, but not from amino acids [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that intestinal anaerobes prefer to assimilate N in the form of peptides or ammonia, rather than as free amino acids [6^8]. Peptides have been shown to stimulate growth of many rumen organisms, for example Prevotella ruminicola utilises N from ammonia or peptides but not amino acids [8,9]. Bacteroides fragilis [10] and Ruminobacter amylophilus [11] also fail to use amino acids as the sole source of energy, however, amino acids are assimilated by these organisms via six transport systems and are rapidly incorporated into cellular material, provided a source of ammonia is available [12].…”
Section: Introductionmentioning
confidence: 99%
“…For many organisms peptides are of considerable nutritional importance, and distinct peptide transport systems have been identified (24,25). In the family of Bacteroidaceae it has been reported that some Bacteroides species are able to grow upon peptides, but not upon free amino acids (13,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Most in vitro studies of peptide and amino acid utilization by rumen bacteria have been conducted with mixed populations (Wallace and Cotta 1988;Broderick et al 1991 ;Russell et al 1991). Some classical studies with single species of bacteria and peptide substrates were published during the 1960s (Pittman and Bryant 1964;Pittman et al 1967), but virtually nothing further was reported until the 1980s, as exemplified by the work of Russell (1983). Even I988), and in particular, Preuotella (formerly Bacteroides) rurninicola (Pittman and Bryant 1964;Pittman et al 1967;Munn et al 1983;Russell 1983;McKain et al 1992;Newbold et al 1992;Wallace et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some classical studies with single species of bacteria and peptide substrates were published during the 1960s (Pittman and Bryant 1964;Pittman et al 1967), but virtually nothing further was reported until the 1980s, as exemplified by the work of Russell (1983). Even I988), and in particular, Preuotella (formerly Bacteroides) rurninicola (Pittman and Bryant 1964;Pittman et al 1967;Munn et al 1983;Russell 1983;McKain et al 1992;Newbold et al 1992;Wallace et al 1993). Furthermore, comparative studies, involving a number of bacterial species, have been limited to examinations of either general biological functions, such as growth efficiency (Cotta and Russell 1982), or very specific attributes, such as peptidase activity (Wallace and McKain 1991;McKain et al 1992).…”
Section: Introductionmentioning
confidence: 99%